2007
DOI: 10.1002/ejsp.370
|View full text |Cite
|
Sign up to set email alerts
|

Disgust, creatureliness and the accessibility of death‐related thoughts

Abstract: From an existential terror management theory perspective, disgusting stimuli are threatening to human beings because they make salient people's vulnerability to death. Two studies were designed to assess this proposition by measuring implicit death-related ideation after individuals were presented with stimuli that either were or were not disgusting, under conditions in which the similarities of humans to other animals or the uniquely human aspects of people were made salient. In Study 1, in which rather extre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 29 publications
2
47
0
Order By: Relevance
“…An encounter with a sick or physically disabled person may serve as a troubling reminder that human life is fragile (Cox, Goldenberg, Pyszczynski, & Weise, 2007;Goldenberg, Heflick, & Cooper, 2008). Thus, studies have shown that MS induces disengagement and mixed emotions toward individuals with disabilities (Ben-Naim, Aviv, & Hirschberger, 2008;Hirschberger, Florian, & Mikulincer, 2005).…”
Section: Terror Management Theory (Tmt)mentioning
confidence: 97%
“…An encounter with a sick or physically disabled person may serve as a troubling reminder that human life is fragile (Cox, Goldenberg, Pyszczynski, & Weise, 2007;Goldenberg, Heflick, & Cooper, 2008). Thus, studies have shown that MS induces disengagement and mixed emotions toward individuals with disabilities (Ben-Naim, Aviv, & Hirschberger, 2008;Hirschberger, Florian, & Mikulincer, 2005).…”
Section: Terror Management Theory (Tmt)mentioning
confidence: 97%
“…Distinguishing ourselves from animals has been suggested by many as a component of the way in which cultural worldviews protect humans from existential anxiety (Beatson & Halloran, 2007;Cox, Goldenberg, Pyszczynski, & Weise, 2007;Goldenberg, Arndt, Hart, & Routledge, 2008;Goldenberg, Cox, Pyszczynski, Greenberg, & Solomon, 2002;Goldenberg, Goplen, Cox, & Arndt, 2006;Goldenberg, Pyszczynski, Greenberg, & Solomon, 2000;Goldenberg et al, 2001;Goldenberg et al, 1999;Koole & Van den Berg, 2005). In the noted studies, participants for whom mortality was made salient exhibited increased denials of human creatureliness relative to control participants, suggesting that thoughts of death caused them to desire distance from their animal natures in an attempt to thwart awareness of physical finitude.…”
Section: Mcglone and Batchelormentioning
confidence: 82%
“…For example, reminders of death led participants to prefer the author of an essay arguing for human uniqueness over the author of an essay arguing that humans are similar to other animals [6]. In addition, priming the similarity between humans and other animals prior to the presentation of disgusting stimuli increased the accessibility of death related thoughts [13]. Further, mortality salience in conjunction with priming human-animal similarity led participants with low levels of trait self-esteem to evaluate animals in general more negatively [33].…”
Section: Discussionmentioning
confidence: 99%
“…Additional support for the Terror Management perspective on disgust comes from the finding that graphic visual images that powerfully elicited disgust increased the accessibility of death related thoughts and that milder disgust eliciting stimuli (reading items from the Disgust Scale) also increased the accessibility of death related thoughts but only when coupled with essays priming human similarity to other animals [13].…”
Section: Terror Management Perspective On Disgustmentioning
confidence: 99%